2020
DOI: 10.1111/jdi.13327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the FreeStyle Libre™ flash glucose monitoring system on glycemic control in individuals with type 2 diabetes treated with basal–bolus insulin therapy: An open label, prospective, multicenter trial in Japan

Abstract: Aims/Introduction: We investigated the effect of FreeStyle Libre TM on glycemic control in Japanese type 2 diabetes patients treated with basal-bolus insulin therapy. Materials and Methods: This prospective, 90-day single-arm study enrolled 94 adults with type 2 diabetes treated with insulin. A 14-day masked baseline phase was followed by an 11-week treatment phase during which participants used the device to monitor glucose levels. The primary end-point was time spent in hypoglycemia (<70 mg/dL) for baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The decreasing number of hypoglycemic events supports this over time (9.54 ± 1.73 3 -6 months before using the flash glucose monitoring system to 0.52 ± 0.50 last six months of the study). These results are consistent with current literature suggesting that the flash glucose monitoring system decreases the incidence of hypoglycemic events [20] [21] [22] [23] [24].…”
Section: Discussionsupporting
confidence: 93%
“…The decreasing number of hypoglycemic events supports this over time (9.54 ± 1.73 3 -6 months before using the flash glucose monitoring system to 0.52 ± 0.50 last six months of the study). These results are consistent with current literature suggesting that the flash glucose monitoring system decreases the incidence of hypoglycemic events [20] [21] [22] [23] [24].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with current literature suggesting that the use of flash glucose monitoring systems decrease the incidence of hypoglycemic events. [12][13][14][15] This study is not without limitations. First, this was a singlecenter study and may not be generalizable to other settings.…”
Section: Discussionmentioning
confidence: 94%
“…Current studies show that flash glucose monitors positively impact the risk of hypoglycemia, treatment satisfaction, and quality of life in various diabetes populations. 7,8,[12][13][14][15] However, the impact of flash glucose monitors on A1C reduction is not as wellestablished, particularly in broader diabetes populations with varying insulin requirements. This ambiguity in treatment effect makes it difficult for clinicians to evaluate the costs and benefits when considering flash glucose monitors for their patients.…”
Section: Introductionmentioning
confidence: 99%
“…There is so far one prospective trial in Japan that demonstrated the effectiveness of Freestyle Libre TM CGM at improving glycaemic control in Japanese type 2 diabetes treated with insulin. 1 Indices of glycaemic control, including time in range, mean glucose and time in hyperglycaemia, were significantly improved. However, the mean total daily dose of insulin was unchanged at the study end.…”
Section: Discussionmentioning
confidence: 97%